Preliminary assessment of liquefiable area in Ermita, Manila using genetic algorithm - Uy, Erica Elice S. (Animo Repository, 2016)
© 2015 IEEE. Liquefaction is a phenomenon that happens when there an excessive ground movement. The original soil structure is destroyed thus weakening its strength. When water is present within the ground, the development of porewater pressure is accelerated due to ground movements also causing the strength of the soil to decrease. Assessment of liquefaction is carried out to Ermita, Manila because of its proximity to Manila Bay. The presence of water makes the area vulnerable to liquefaction. Genetic algorithm is incorporated in the computation of the factor of safety against liquefaction. Parameters considered in genetic algorithm are depth of soil with respect to the ground surface, N60, fines content, unit weight and stress reduction coefficient. The factor of safety computed from genetic algorithm yield an error of 0.6%. © 2015 IEEE.